Progesterone Receptor Expression Declines in the Guinea Pig Uterus during Functional Progesterone Withdrawal and in Response to Prostaglandins - Welsh, Toni N. (Public Library of Science, 2014)
Progesterone withdrawal is essential for parturition, but the mechanism of this pivotal hormonal change is unclear in women and other mammals that give birth without a pre-labor drop in maternal progesterone levels. One possibility suggested by uterine tissue analyses and cell culture models is that progesterone receptor levels change at term decreasing the progesterone responsiveness of the myometrium, which causes progesterone withdrawal at the functional level and results in estrogen dominance enhancing uterine contractility. In this investigation we have explored whether receptor mediated functional progesterone withdrawal occurs during late pregnancy and labor in vivo. We have also determined whether prostaglandins that induce labor cause functional progesterone withdrawal by altering myometrial progesterone receptor expression. Pregnant guinea pigs were used, since this animal loses progesterone responsiveness at term and gives birth in the presence of high maternal progesterone level similarly to primates. We found that progesterone receptor mRNA and protein A and B expression decreased in the guinea pig uterus during the last third of gestation and in labor. Prostaglandin administration reduced while prostaglandin synthesis inhibitor treatment increased progesterone receptor A protein abundance. Estrogen receptor-1 protein levels remained unchanged during late gestation, in labor and after prostaglandin or prostaglandin synthesis inhibitor administration. Steroid receptor levels were higher in the non-pregnant than in the pregnant uterine horns. We conclude that the decreasing expression of both progesterone receptors A and B is a physiological mechanism of functional progesterone withdrawal in the guinea pig during late pregnancy and in labor. Further, prostaglandins administered exogenously or produced endogenously stimulate labor in part by suppressing uterine progesterone receptor A expression, which may cause functional progesterone withdrawal, promote estrogen dominance and foster myometrial contractions.